Pemanfaatan Media Presentasi Powerpoint dalam Meningkatkan Minat Belajar Bahasa Inggris Siswa Madrasah Tsanawiyah - Syarif Hidayat; Hesty Widiastuty (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This study aims to enhance students' interest in learning English through the utilization of PowerPoint presentations as a teaching medium. The research was conducted at MTs Hidayatul Muhajirin Palangka Raya, involving eighth-grade students. The method employed was a lecture using PowerPoint presentations equipped with audio features. The material taught was "Descriptions of People’s Personalities." The results showed that the use of PowerPoint presentations was able to increase students' motivation and interest in learning. The visually appealing materials, complemented by audio features, along with group discussions and individual assignments, effectively accommodated various learning styles, particularly visual and auditory. Additionally, PowerPoint facilitated students' understanding of concepts, vocabulary, and English grammar. In conclusion, the utilization of PowerPoint presentations as a teaching medium is an effective step in improving the quality of English language learning.